A genome-wide association scan of biological processes involved in oral lichen planus and oral squamous cell carcinoma. Issue 25 (June 2017) - Yang, Qiaozhen; Xu, Beiyun; Sun, Hongying; Wang, Xiaxia; Zhang, Jie; Yu, Xuedi; Ma, Xiaojuan
Abstract: Background: In this study, the molecular mechanisms underlying malignant transformation from oral lichen planus (OLP) to oral squamous cell carcinoma (OSCC) were examined. Methods: High-throughput sequencing of long noncoding RNAs (lncRNAs) and mRNAs of normal subjects and patients with OLP and OSCC was conducted. RNA-seq reads were mapped, lncRNA and mRNA transcripts were assembled, and expression levels were estimated. The targets of lncRNAs were predicted. Finally, Gene Ontology (GO) and pathway enrichment analyses of differentially expressed genes (DEGs) and lncRNA targets were performed. Results: High-quality sequence data were generated and the mapping ratios for OSCC, normal, and OLP samples were high. In total, 820, 656, and 582 DEGs were obtained from OPL vs. normal, OSCC vs. normal, and OSCC vs. OPL, respectively. A total of 1721 known lncRNAs and 133 predicted lncRNAs and targets were obtained. Keratinization was significantly enriched by OSCC-related DEGs, but not OPL-related DEGs. The pathway of olfactory transduction was enriched by OPL- and OSCC-related DEGs. Defense response to virus and viral carcinogenesis were enriched by DEGs and lncRNA targets in all comparisons. GO term related to the metabolic process was enriched by lncRNA targets in the OPL vs normal comparison, and antigen processing and presentation via MHC class I was significantly enriched by lncRNA targets in the other 2 comparisons. Conclusion: Keratinization and MHC class I antigen processing and presentation were activated during the malignant transformation from OLP to OSCC. Additionally, the olfactory transduction pathway may be important for OSCC. Abstract : Supplemental Digital Content is available in the text